2011
DOI: 10.1007/s11274-010-0644-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of daptomycin production in Streptomyces roseosporus LC-51 by manipulation of cofactors concentration in the fermentation culture

Abstract: The effects of eight cofactors of enzymes on daptomycin production were investigated in this work, which included nicotinic acid (VPP), riboflavin (VB 2 ), heme, thiamine (VB 1 ), biotin (VH), cyanocobalamin (VB 12 ), tetrahydrofolic acid (THF) and pyridoxal 5-phosphate (VB 6 ). The dry cell weight (DCW), consumption of glucose, and daptomycin production were obviously improved when proper amount of exogenous cofactors were supplemented in the medium. The effects of heme, THF, VB 12 and VB 6 on daptomycin prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The result is in agreement with the findings of Kreig and Holt [43], who reported that fermentable carbon sources by Streptomycetes induced both growth and antibiotic production. The above results also indicated the relationship between the antibiotic production and both glycolysis and pentose phosphate pathways, which are known to be aerobically NADH-, ATP-, and NADPHgenerating systems, respectively [44].…”
Section: Discussionmentioning
confidence: 58%
“…The result is in agreement with the findings of Kreig and Holt [43], who reported that fermentable carbon sources by Streptomycetes induced both growth and antibiotic production. The above results also indicated the relationship between the antibiotic production and both glycolysis and pentose phosphate pathways, which are known to be aerobically NADH-, ATP-, and NADPHgenerating systems, respectively [44].…”
Section: Discussionmentioning
confidence: 58%
“…N-decanoic acid was fed at 48 h after inoculation (0.2 g/l). All experiments were done in triplicate 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Cofactors were added to the sterile culture medium after aseptic filtration. Eight cofactors were added which included nicotinic acid(4 mg/l), riboflavin(0.5 mg/l), heme(9 mg/l), thiamine(0.4 mg/l), biotin(0.1 mg/l), cyanocobalamin(0.04 mg/l), tetrahydrofolic acid(6 mg/l) and pyridoxal 5-phosphate(0.4 mg/l) (Yu et al 2011 ). As for the airlift bioreactor, the pH was automatically controlled at 7.0 with 8 M NaOH solution and the aeration speed of 1 v/v/m for 6 days.…”
Section: Methodsmentioning
confidence: 99%